Physicochemical and biological factors determining the patchy distribution of soil water repellency among species of dominant vegetation in loess hilly region of China - Chai, Xiaohong; Xu, Xuexuan; Li, Lushan; Wang, Weiwei; Li, Shuo; Geming, Palixiati; Qu, Yuanyuan; Zhang, Qi; Ren, Xiuzi; Xu, Yuanhui; Li, Mengyao (Frontiers in Plant Science, 2022)
Soil water repellency (SWR) shows a physical phenomenon that water cannot or is difficult to penetrate into soil surface. There are many factors involved in its occurrence, but which is the main one for the emergence of SWR in loess remains unclear. In this work, we have studied a large number of physicochemical and biological factors under the influence of different dominated vegetations (Pinus tabulaeformis Carr., Robinia pseudoacacia L. and Hippophae rhamnoides L.) in hilly loess region by gas chromatography-mass spectrometry (GC-MS) and high-throughput sequencing techniques. We observed severely and extremely water-repellent soils under Pinus, while only slightly or strongly water-repellent soils under Robinia and Hippophae. The three main compounds in water-repellent soils were fatty acids, alkanols, and alkanes, of which fatty acids and alkanols were positively correlated with SWR, whereas alkanes had no relationship with SWR. High-throughput sequencing revealed that the abundance of Basidiomycota under Pinus was higher than that under Robinia and Hippophae. In addition, we further investigated the relationship between each factor through redundancy analysis (RDA) and found that SWR and alkanols were strongly associated with bacterial or fungal community composition, to be precise, that was closely linked to Actinobacteria in bacteria and Basidiomycota in fungi. Also, the correlation between SWR and alkanols was the strongest regardless of bacterial or fungal community. Here, we show that polar waxes (especially alkanols) generated by plants may be responsible for the development of SWR in loess, as well as their interactions with microbes when the topsoil is close to air-drying. Our findings have guiding significance for soil and water conservation in loess hilly region of China. However, there is a need for further testing on different plant species or land uses.